AWARENESS OF CLINICAL APPLICATIONS OF VITAMIN K AMONG DENTAL STUDENTS - E, Nandakumar.; Ganapathy, Dhanraj; Kumar Pandurangan, Kiran; Velayudhan, Ashok (International Journal of Psychosocial Rehabilitation, 2020)
Background: Vitamin K was first identified in 1936 to be a key factor in blood clotting. When chickens were fed a low-fat diet, they exhibited significantly lower coagulation capacity, resulting in severe bleeding. The lipid fraction of diet was analyzed, and a novel antihemorrhagic factor was discovered. This lipid-soluble factor was given the first letter in the alphabet available, which coincided with the first letter of the German word koagulation, and was deemed to be only essential for its anti-haemorrhagic trait. Since then, non-coagulant functions have been discovered and have attracted research interest in several fields around the world. Vitamin K occurs as two vitamins: vitamin K1 (also known as phylloquinone) and vitamin K2 (designated also as menaquinones (MKs). AIM: To evaluate and compare the awareness of clinical application of vitamin K among dental students. MATERIALS AND METHODS A cross-sectional survey was carried among 100 dental practitioners using a questionnaire. Questionnairecontained 10 questions on awareness of clinical applications of vitamin E among dental students. The data were extracted and analysed. Conclusion: The purpose of the study is to create awareness of clinical applications of vitamin K among dental students.